Determinants of Parental School Selection for Early Childhood Education: A Confirmatory Factor Analysis (CFA) Approach - Riana, Neti; Syamsudin, Amir (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
Choosing the most suitable education for their children is often challenging for parents due to the many factors that must be considered. The desire to find the ideal kindergarten is complicated by the need to meet various criteria, leading to confusion and difficulty in decision-making. This study addresses this complexity by employing Confirmatory Factor Analysis (CFA) to simplify selection. Focusing on TKIT Al Farabi, the research validates a hypothesised model comprising ten critical factors: location, accreditation, facilities, fees, curriculum, religious education, teacher competence, extracurricular activities, school order and cleanliness, and alumni achievements. Data were collected from 154 parents through a structured questionnaire and analysed using SPSS software. The CFA results confirmed five dominant factors: school excellence, teacher professionalism, education costs, social development, and language development, collectively explaining 60.9% of the total variance. The study demonstrates that the CFA method effectively aids parents in making quick and accurate decisions regarding early childhood education. The findings also emphasise the significance of academic and non-academic attributes in school selection, suggesting that educational institutions should adopt more holistic curricula. These results have substantial implications for policymakers and educational administrators, underscoring the need for integrated programs that align with the diverse expectations of parents. Despite the study's valuable insights, further research in diverse settings is recommended to enhance the generalizability of the findings.